METAMORPHOSIS OF HIGHER EDUCATION: A MULTIDIMENSIONAL ANALYSIS OF THE DIGITAL DISRUPTION, MOOCS, AND THE SHIFTING UNIVERSITY PARADIGM - Siminto; Alim Hardiansyah; Abdul Wahab Syakhrani; Suhana Sarkawi; Aat Ruchiat Nugraha (Adisam Publisher, 2023)
In a dynamic digital transformation era, this comprehensive study delved into the metamorphosis of higher education, exploring the multifaceted impact of digital disruption and the emergence of Massive Open Online Courses (MOOCs). The research incorporated diverse data sources, unveiling profound changes that reshaped the traditional university landscape. Historical developments were meticulously analyzed, revealing the inception of online learning and its transformative journey from an experimental novelty to a mainstream educational tool. Technological advancements played a pivotal role in shaping these shifts in teaching and learning, with faculty adapting to a student-centric approach characterized by personalized learning, adaptive assessment, and blended learning environments. The rise of MOOCs took center stage, scrutinizing the MOOC ecosystem, global impact, and disruptive challenges they presented. Leading platforms and providers were central in extending education worldwide and bridging educational divides. Complex challenges included the impact of MOOCs on traditional higher education and debates surrounding accreditation. This study encompassed the strategic adaptations of universities as they embraced hybrid learning programs, competency-based education, and partnerships with online platforms. Quality assurance measures ensured academic rigor and accreditation standards were preserved. Faculty members underwent transformative changes in their roles, engaging in professional development and endorsing technological adoption. Further exploration in this ever-evolving paradigm is invited, as this study, rooted in a rich tapestry of data and multidimensional multidimensional analysis, provided a profound understanding of the metamorphosis characterizing higher education.